The functioning of the Cuban home hospitalization programme: a descriptive analysis - Bonet Mariano; Rodríguez Armando; Barroso Isabel; De Vos Pol; Van der Stuyft Patrick (BMC, 2007)
Abstract Background Over the last decades hospital at home (HaH) programmes have been set up in many, mainly European, countries. The Cuban HaH programme is not hospital driven, but the responsibility of the first line health services, and family doctors play a pivotal role. Methods We analyse the structure and functioning of the Cuban programme. In this descriptive study, information was prospectively collected on HaH patients admitted between July 1st 2001 and June 30th 2002. Results Admission rates varied between areas from 0.014 to 0.035 per person per year (ppy). The < 1y and 1-4y age groups had the highest admission rates. In one area the follow-up of pregnancy problems led to high 15-24y and 25-49y female admission rates (0,070 and 0,058 respectively). Respiratory affections were the most frequent reason for admission (32,6%), followed by early hospital discharge (16,0%) and gynaeco-obstetrical problems (10.8%). The median length of stay varied from 5 to 7 days between regions and from 5 days (early discharge) to 7 days (gynaeco-obstetrical problems) in function of the reason for admission. On average an HaH episode entailed 1.4 and 1.6 contacts per patient-day with the family doctor and nurse respectively. Conclusion Difference in admission criteria in function of geography, distance to the hospital, transport facilities, and staff factors, as well as differences in hospital policy on early discharge explain the observed variability. The programme plays an important role in the integrated approach to quality care in the Cuban health system, but could benefit from more uniform admission criteria.